CLCNt2 Mediates Nitrate Content in Tobacco Leaf, Impacting the Production of Tobacco-Specific Nitrosamines in Cured Leaves - Bovet, Lucien; Campanoni, Prisca; Lu, Jian; Hilfiker, Aurore; Kleinhans, Samuel; Laparra, Hélène; Schwaar, Joanne; Lewis, Ramsey S.; Matsuba, Yuki; Ma, Hong; Dewey, Ralph E.; Goepfert, Simon (Frontiers in Plant Science, 2022)
Nitrate accumulation in tobacco (Nicotiana tabacum L.) leaf, particularly in the burley (BU) type, is a reservoir for the generation of nitrosating agents responsible for the formation of tobacco-specific nitrosamines (TSNAs). TSNAs are mainly produced via the nitrosation of alkaloids occurring during the curing of tobacco leaves. Additional formation of TSNAs may also occur during tobacco storage, leaf processing and in some circumstances via pyrosynthesis during combustion. Two TSNA species, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N-nitrosonornicotine (NNN) are found in the tobacco products and have been documented to be animal carcinogens. A previous study showed that decreasing the accumulation of nitrate in tobacco leaf via the overexpression of a deregulated form of nitrate reductase is efficient to reduce the production of TSNAs. We pursue in finding another molecular genetic target to lower nitrate in BU tobacco. Suppressing expression or knocking-out CLCNt2 has a direct impact on leaf nitrate and TSNA reduction in cured leaves without altering biomass. This study provides now a straight path toward the development of new commercial tobacco varieties with reduced TSNA levels by breeding of variants deficient in active CLCNt2 copies.